Asthma: personalized and precision medicine. Issue 1 (February 2018) - Canonica, Giorgio W.; Ferrando, Matteo; Baiardini, Ilaria; Puggioni, Francesca; Racca, Francesca; Passalacqua, Giovanni; Heffler, Enrico
Abstract : Purpose of review: In this review, we herein describe the progress in management of severe asthma, evolving from a 'blockbuster approach' to a more personalized approach targeted to the utilization of endotype-driven therapies. Recent findings: Severe asthma characterization in phenotypes and endotypes, by means of specific biomarkers, have led to the dichotomization of the concepts of 'personalized medicine' and 'precision medicine', which are often used as synonyms, but actually have conceptual differences in meaning. The recent contribute of the omic sciences (i.e. proteomics, transcriptomics, metabolomics, genomics, …) has brought this initially theoretic evolution into a more concrete level. Summary: This step-by-step transition would bring to a better approach to severe asthmatic patients as the personalization of their therapeutic strategy would bring to a better patient selection, a more precise endotype-driven treatment, and hopefully to better results in terms of reduction of exacerbation rates, symptoms, pulmonary function and quality of life.